PENINGKATAN HASIL BELAJAR IPAS MATERI “BAGAIMANA BENTUK INDONESIAKU?” MENGGUNAKAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT BERBANTUAN MEDIA WORDWALL PADA PESERTA DIDIK KELAS V SDN 021 SUNGAI KUNJANG TAHUN PEMBELAJARAN 2023/2024 - Genggang, Tiara Petri Cicilia; Wahyuningsih, Tri; Makmun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to improve the science learning outcomes of grade V students, particularly in the material "What is the shape of my Indonesia?" through the Teams Games Tournament learning model, assisted by Wordwall media. This study focuses on class VB students of SDN 021 Sungai Kunjang in the 2023/2024 academic year. The research is conducted using Classroom Action Research (CAR), carried out in three cycles, each with two meetings. The four stages of the procedure include planning, implementation, observation, and reflection. The study involves teachers and 29 students from class VB of SDN 021 Sungai Kunjang. Data collection methods include observation, testing, and documentation. Instruments used include teacher and student activity sheets, and learning outcome tests. The data analysis techniques used are average, percentage of completion, improvement in learning outcomes, and value conversion. The findings show significant improvement in learning outcomes. In the initial data, the average score was 66.83, increasing to 67.07 in Cycle I, with a 0.36% improvement and 44.83% completion. In Cycle II, the average score rose to 75.00, with a 12.22% increase and 84.76% completion. In Cycle III, the average score increased to 86.21, reflecting a 29.00% improvement and 93.10% completion. These results indicate a positive effect of the Teams Games Tournament model assisted by Wordwall media on improving science learning outcomes.